2007
DOI: 10.1111/j.1651-2227.2007.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Satisfactory long‐term results after Nissen fundoplication

Abstract: The majority of parents were satisfied with the long term results of the Nissen fundoplication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 19 publications
3
26
0
Order By: Relevance
“…Parents also reported better well-being of neurologically impaired children after fundoplication. Kristensen et al (7) also reported good parental satisfaction after fundoplication. O'Loughlin et al (27) surveyed 89 caregivers following antireflux surgery in neurologically impaired children.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Parents also reported better well-being of neurologically impaired children after fundoplication. Kristensen et al (7) also reported good parental satisfaction after fundoplication. O'Loughlin et al (27) surveyed 89 caregivers following antireflux surgery in neurologically impaired children.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, there is a considerable discrepancy between the parents' perceptions and our evaluated post-operative data, as described above. Improvements from severe vomiting, better quality of sleep and a reduced number of episodes of pneumonia are plausible explanations for the positive outcome (7). Interestingly, caregivers reported significant improvement in feeding indices and perceptions of child 0 s comfort and child 0 s quality of life (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, there has only been performed one other RCT in children comparing LF and OF. 12,17,26,[32][33][34] Because not all patients with recurrence are reoperated, many studies are underpowered to detect any difference in recurrence rate between the 2 methods. 12 Although there is a lack of RCTs in children comparing the 2 operative methods, several nonrandomized publications do not suggest inferior results after LF than after OF in children.…”
Section: Discussionmentioning
confidence: 99%
“…There is significant heterogeneity among pediatric GERD studies [1]. Surgical treatment for GERD is reported to improve quality of life, especially for neurologically impaired children [2,3]. Despite initial symptomatic relief, however, the incidence of redo operation after fundoplication is reported between 1.7 and 18 percent [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%